Análise temporal comparativa da estrutura vegetal do mangue do estuário do rio Curu (Ceará) e o uso de sensoriamento remoto como subsídio para a gestão ambiental - Benevides, Jorgeana de Almeida Jorge (2024)
Mangroves are legally protected due to their ecological, economic and social importance. However, the advancement of anthropogenic pressures on these ecosystems has been interfering with their ecosystem goods and services. Among the stressors on the Curu River Mangrove is the suppression of vegetation for the installation of shrimp farms and agriculture. The use of Remote Sensing has settled as a useful tool in monitoring conditions and changes in coastal areas. With this, a temporal analysis of the mangrove structure of the Curu River estuary was carried out as a base for monitoring environmental quality, based on data collected in the years 2007 and 2021. The activity of estuarine vegetation was also evaluated through multitemporal analysis of Landsat images between the years 2000 and 2020 based on three vegetation indices: NDVI, SAVI and IAF. Regarding the phytosociological parameters evaluated, Rhizophora mangle was the species that stood out in both periods. This mangrove appears to be undergoing a natural regeneration process given the numbers of juveniles observed in the second survey. This characteristic had an impact on the results of DAP and basal area, which showed significant differences between the years. The responses from the Indexes showed that the flora underwent significant changes in terms of distribution, density and health in 14 years, such as the longitudinal expansion of the mangrove, progressive replacement by crops of commercial interest and lower NDVI in the areas surrounding the crops. The complementarity in the responses observed by the Indexes and the field data presented itself as an efficient tool for evaluating the conditions of the flora in relation to the main environmental impacts in the area, in order to be applied in local coastal planning and management.